ANALISIS CITRA DIGITAL UNTUK SAMPEL BATUAN MENGGUNAKAN MICRO-CT SCANNER SKYSCAN 1173 - Aceng Kurnia Rochmatulloh; Ulpa Zein Fawziah; Rizki Fahmi Sumaryono; Selly Feranie; Fourier Dzar Eljabbar Latief (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Digital image analysis has been done on rock samples of scanning results using Bruker Skyscan 1173 Micro-CT Scanner. The analysis is done qualitatively and quantitatively to know the characteristics of the sample image of the rock. The digital samples of rock produced from the scanning process are 380 x 380 x 380 pixels in size. Qualitative analysis is done by using CTAn (2D) and CTVox (3D) software. Quantitative analysis is done by calculating pore size, open porosity, closed porosity, total porosity and fractal dimension using CTAn software. The consensus analysis of the use of Cartesian axes of digital data in the software used (CTAn, CTVox, DataViewer, ImageJ and Matlab) is done by examining 2D trans-axial imagery (XY), sagittal (field ZY), and coronal (XZ). The results of the rock parameters analyzed in the rock samples indicate that the rocks belong to the type of faneric/fine fanerokristalin, have a porosity that is special, the pores in the rock are well connected, and the fluid flow in the rock is quite complex. Rock samples obtained from various software show similarities of image on CTAn, CTVox, and DataViewer software, but unlike the image of ImageJ and Matlab so it is necessary to change the coordinate axis if in advanced processing using both devices. Keywords: digital image analysis, porosity, fractal dimension, porous media